OVULATION RATE USING GONADOTROPIN RELEASING HORMONE AND SEMINAL PLASMA IN ALPACAS AND LLAMAS - Mamani C., Rubén (2013)
The aim of the present study was to determine the ovulation rate using GnRH (buserelin) and seminal plasma of alpaca as ovulation inductors in alpacas and llamas. For this, 93 alpacas and 92 llamas were distributed in two groups: a group treated with buserelin (42 μg) IM, and a group treated with 1 ml of seminal plasma IM (50/50% seminal plasma of alpaca and PBS + antibiotics). The ovulation rate was 78.7 and 88.9% in alpacas and 80.6 and 70.0% in llamas using buserelin and seminal plasma respectively; and without statistical differences due to type of ovulation inductor, ovary carrying the preovulatory follicle or species.